Penggunaan mobile apps sebagai kewajiban hukum untuk memantik ketertarikan pengguna bank syariah - jumaini, Jumaini (Maliki Interdisciplinary Journal, 2025)
Bank Syriah Indonesia is here to provide convenience for the Indonesian people in transacting according to sharia principles, sales services become very important when competition between banks is getting tighter. Therefore, the development of an information system is very important to facilitate service to consumers. The development of a service system through mobile banking has a reciprocal impact between customers and the bank. The advantages of mobile banking have a general and wide reach, in addition the information presented can be displayed in detail in 1 application. The result of this discussion is the government’s regulation in regulating its citizens as BSI customers to use BSI mobile banking, so that over time other citizens will also be interested in significant changes.